Correlation between actual nutrition and lipid peroxidation and antioxidant defense parameters in aged 14–17 years adolescents living in rural area - M. A. Darenskaya; L. V. Rychkova; T. A. Astakhova; A. V. Pogodina; O. N. Dolgikh; Yu. N. Klimkina; L. I. Kolesnikova (Сибирский научный медицинский журнал, 2022)
The aim of the study was to reveal the relationship between the parameters of actual nutrition and the lipid peroxidation and antioxidant defense system in adolescents aged 14–17 in a rural area. Material and methods. 76 adolescents aged 14–17 of the Irkutsk region were examined by the cross-sectional study method. Actual nutrition was studied by the 24-hour nutrition reproduction method. The content of substrates with unsaturated double bonds (DB), diene conjugates (DC), ketodienes and conjugated trienes (KD and CT), thiobarbituric acid reacting species (TBARS), α-tocopherol, retinol, reduced (GSH) and oxidized glutathione (GSSG), total blood antioxidant activity (TAA), superoxide dismutase (SOD) activity in blood by spectrophotometry and fluorometry methods were analyzed. Results. The adolescents’ diet did not meet the principles of a balanced diet – there was reduced protein intake, an imbalance of unsaturated fatty acids, A, C, D, B vitamins deficiency. An excessive element in the diet was sodium. The content of substrates with DB, KD and CT and TBARS increased significantly in the studied group of adolescents, the concentration of DC decreased. Parameters of antioxidant defense both decreased (TAA, retinol content) and increased (α-tocopherol, GSH concentration). Correlation analysis showed relationships between DB and vitamin B1, B2 content; DC level and calories, carbohydrate and vitamin B1 content; concentration of KD and CT and fats, TAA and vitamin A and β-carotene level; level of α-tocopherol in blood and vitamin E in food; GSH and vitamin K; SOD activity and vitamin H content. Multiple negative correlations were between GSSG and fat, vitamins B1, B9, C, K food concentration were found.Conclusions. The calculated vitamin consumption indicators allow to reveal nutritional deviations in adolescents and to connect them with the real provision of the body with these metabolites.